Analisis Indeks Pencemaran Air Pada Area Pertambangan Rakyat Di Sungai Takaras Kelurahan Petuk Barunai Kecamatan Rakumpit Kota Palangka Raya Provinsi Kalimantan Tengah: ANALYSIS OF WATER POLLUTION INDEX IN MINING AREA IN TAKARAS RIVER, PETUK BARUNAI SUBDISTRICT, RAKUMPIT SUBDISTRICT - FEBRI INDRIANTO; Sukmawatie, Neny; Indrajaya, Fahrul; Saptarwatono; Fidayanti, Neny (JURNAL TEKNIK PERTAMBANGAN, 2023)
The research was conducted at an unlicensed gold mining location in Petuk Barunai Village, Rakumpit District, Palangka Raya City. This study aims to determine the quality of Takaras River water based on the results of testing Takaras River water samples in the laboratory and to analyze the Water Pollution Index in the community mining area in the Takaras River. The Pollution Index is systematically an index related to polluting compounds that are meaningful for a designation. This research begins by analyzing 3 samples of Takaras River water affected by gold mining and then testing the samples in the laboratory. Processing data obtained from laboratory test results from each parameter tested to obtain values to determine Water Quality and compare with Water Quality Standards.The river water parameters to be studied are pH of Takaras River water, Hg, Pb, Cu, Fe, Cd, TDS, TSS, BOD, COD and DO. Parameters that comply with class II water quality standards are Fe, Cd, Pb, TDS and DO. While the parameters that pass class II water quality standards are Hg, Cu, pH, TSS, BOD, and COD. Based on the Pollution Index analysis, the Takaras River is included in the Moderately Polluted category (Fairly Polluted) with IP results of 6.23. Keywords: Pollution Index, Takaras River, Water Quality, Gold Mining